Penerapan Metode Pembelajaran Kooperatif Student Team Achievment Division untuk Meningkatkan Motivasi dan Hasil Belajar Siswa di SMA Negeri 1 Tanjung - Astawa, I Nyoman Budhi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2022)
This study aims to improve student motivation and learning outcomes at SMA Negeri 1 Tanjung. through the application of the Student Team Achievment Division (STAD) learning method. This research method used classroom action research which is carried out in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The data collection technique in this study used observation sheets, questionnaires and tests. The data analysis technique of this research used descriptive qualitative and quantitative analysis. The results showed that: in the pre-cycle student learning mastery was 70%, in the first cycle student learning motivation was 78.12%, for teacher activities it was 79.16%, while for classical learning completeness it was 72.72%, while in the second cycle learning motivation was students increased to 84.37%, for teacher activity increased to 83.33%, while for classical learning completeness increased to 87.87%. So with these results it can be concluded that through the application of the Student Team Achievment Division (STAD) method can increase student motivation and learning outcomes.